ҚАРАҚАЛПАҚ ХАЛЫҚ АЎЫЗЕКИ ДƟРЕТПЕЛЕРИНДЕГИ АРАБЛЫҚ ШЫҒЫСҚА ИЙЕ АНТРОПОНИМЛЕР - Даниярова, З.Ж. (SCIENCE and SOCIETY, 2020)
The article states that the Karakalpak language was under influence of Persian, and then, due to the intensive influence of the Arabic language, it borrowed many Persian, Arabic and other words through them. Therefore, Arabic human names in the language of folklore were chosen as the object of study. Anthroponyms are concerned with determining the linguistic appearance and nationality of the people’s culture. Examples are given of the use of anthroponyms in the language of folklore as names that occur in our daily life.